Analysis of Tabarru' Fund Governance and Claims Management from the Perspective of The Sustainability of the Performance of Sharia Life Insurance Companies at PT Asuransi Jiwa Syariah Bumiputera - Muhammad Fikri Pohan; Andri Soemitra; Nur Ahmadi Bi Rahmani (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the relationship between tabarru’ fund governance and claims management from the perspective of sustainable performance of Islamic life insurance companies at PT Asuransi Jiwa Syariah Bumiputera using a qualitative Systematic Literature Review (SLR) method. The literature was collected through Google Scholar supported by the Publish or Perish application and selected based on inclusion and exclusion criteria within the 2020–2026 period, resulting in 17 relevant articles. The findings indicate that effective tabarru’ fund governance—through fund separation, sharia compliance, transparency, accountability, prudential principles, and ta’awun—plays a strategic role in maintaining financial stability and improving company performance, while efficient claims management aligned with contracts and policy provisions enhances participant trust and satisfaction. The study further confirms a reciprocal relationship between proper tabarru’ fund management and effective claims management in supporting the operational sustainability and reputation of Islamic life insurance companies.